Gianyar Botanical Garden Development Strategy as a Tourism Attraction Based on Local Wisdom in Kerta Tourism Village, Payangan District, Gianyar Regency - Kartimin, I Wayan; Purnama Dewi, Desak Made; Budhayana, I Wayan (Akademi Komunitas MAPINDO, 2023)
Gianyar Botanical Gardens is one of the natural attractions located in Gianyar Regency. The Gianyar BotanicalGardens has beautiful, cool and still beautiful natural potential that provides comfort for visitors to touristattractions, and has supporting potential such as cultural tourism and local wisdom such as the Bali Agatradition, Bali Age Architecture, and Gelagar Dance where this local wisdom is only owned by Kerta TourismVillage. In the development there are problems that hinder its implementation, including budget limitations forthe cost of facilities and infrastructure for tourist objects such as infrastructure, road conditions and otherfacilities that support the existence of the Gianyar Botanical Gardens tourist attraction. Lack of promotion oftourist objects, the need for empowerment of local communities about tourism and tourism development. Thisstudy aims to analyze the right strategy in the development of the Gianyar Botanical Gardens tourism object.The method used in this study is a qualitative method with a descriptive approach. This study uses a theorybased on a SWOT analysis. The results of this study indicate that the right strategy to be used in thedevelopment of the Gianyar Botanical Gardens is a strategy for utilizing natural potential, cultural tourism andlocal wisdom to support the existence of the Gianyar Botanical Garden tourism object to increase touristattraction in Gianyar Regency, a strategy for strengthening local community awareness institutions indevelopment of tourism objects and strategies to increase the capacity and role of rural communities throughthe village government in developing tourism objects of the Gianyar Botanical Gardens.Keywords: Strategy, Development, Garden, Local Wisdom